Home-quarantine during the initial Covid-19 outbreak in Israel: parent perceived impact on children with ASD. Issue 6 (June 2022) - Arazi, Ayelet; Koller, Judah; Zachor, Ditza A.; Golan, Ofer; Sadaka, Yair; Eytan, Dganit; Stolar, Orit; Atzaba-Poria, Naama; Golan, Hava; Menashe, Idan; Meiri, Gal; Gabis, Lidia V.; et al.
Abstract: Background: Studies have reported that Covid-19 home-quarantine periods have had mostly negative psychological impact on children with ASD and their families. Here we examined parent perceived impact of a 6-week quarantine period imposed in Israel at the beginning of the Covid-19 outbreak, in mid-March 2020. Methods: An anonymous online questionnaire was completed by parents of 268 children with ASD. Parents rated deterioration/improvement in their child's behaviors, abilities, mood, sleep, and anxiety along with changes in their own mood, sleep, parenting skills, and family relationships. We performed t-tests and ANOVA analyses to assess the significance of perceived impact on each domain and potential differences in the impact across families with children of different ages, genders, and levels of required support as well as families that experienced different magnitudes of economic hardships. Results: Parents reported significant deterioration in their mood and sleep along with significant improvements in relationships with their spouse and child with ASD, and in their parenting skills. Parents also reported significant increases in the severity of tantrums, anxiety, and restricted and repetitive behavior symptoms along with significant improvements in social and communication abilities of their child with ASD. Ratings were significantly lower in families of ASD children who regularly require more support and in families that experienced economic hardships. Conclusions: While periods of home-quarantine create numerous hardships for families of children with ASD, they may also offer an opportunity for improving parenting skills, family relationships, and children's social communication abilities with potential relevance for improving remote services. Abstract : Covid-19, Quarantine, Lockdown, Corona, Psychological impact, Support.